Myasthenia Gravis With Reversible Pyramidal Tract Damage and Pseudo Internuclear Ophthalmoplegia. A Case Report and Literature Review - Weng, Yinghong; Min, Yan; Sheng, Zhenghe; Li, Jia; Huang, Dehong (Frontiers in Neurology, 2019)
Myasthenia gravis (MG) is a rare and treatable antibody-mediated autoimmune disease. Pseudo internuclear ophthalmoplegia (-INO) or pyramidal tract damage is rarely observed in MG, and there were no known cases of MG with both pseudo-INO and pyramidal tract damage. Here, we report a case of a 61-year-old female suffering from MG accompanied by pseudo-INO and pyramidal tract damage with a rapid progressive course. Her blood and cerebrospinal fluid tests were normal, except for the presence of the anti-acetylcholine receptor antibody. CT and contrast enhancement of the chest showed a thymic involution. MRI and contrast enhancement images of the brain and whole spine were normal. Both the clinical response to the administration of neostigmine and the repetitive nerve stimulation test were positive. The motor evoked potentials at lower limbs recording were normal. According to her signs, symptoms, decrementing response on repetitive stimulation test, elevated anti-acetylcholine receptor antibody and positive response to neostigmine, the patient was diagnosed as having MG. After treatment with pyridostigmine, intravenous immunoglobulin, prednisone acetate tablets and methotrexate, all her symptoms disappeared, including pseudo-INO and pyramidal tract damage. To our best knowledge, this is the first report of a case of MG with both pseudo-INO and pyramidal tract damage. Based on our case and a review of the literature, we propose that pyramidal tract damage and pseudo-INO can be two signs of MG, and that MG can cause damage to other systems besides neuromuscular junctions.